Enhanced seedling growth by 3‐n‐pentadecylphenolethanolamide is mediated by fatty acid amide hydrolases in upland cotton (Gossypium hirsutum L.). (12th July 2022) - Arias‐Gaguancela, Omar; Adhikari, Bikash; Aziz, Mina; Chapman, Kent D.
Abstract: Fatty acid amide hydrolase (FAAH) is a conserved amidase that is known to modulate the levels of endogenous N ‐acylethanolamines (NAEs) in both plants and animals. The activity of FAAH is enhanced in vitro by synthetic phenoxyacylethanolamides resulting in greater hydrolysis of NAEs. Previously, 3‐ n ‐pentadecylphenolethanolamide (PDP‐EA) was shown to exert positive effects on the development of Arabidopsis seedlings by enhancing Arabidopsis FAAH (AtFAAH) activity. However, there is little information regarding FAAH activity and the impact of PDP‐EA in the development of seedlings of other plant species. Here, we examined the effects of PDP‐EA on growth of upland cotton ( Gossypium hirsutum L. cv Coker 312) seedlings including two lines of transgenic seedlings overexpressing AtFAAH . Independent transgenic events showed accelerated true‐leaf emergence compared with non‐transgenic controls. Exogenous applications of PDP‐EA led to increases in overall seedling growth in AtFAAH transgenic lines. These enhanced‐growth phenotypes coincided with elevated FAAH activities toward NAEs and NAE oxylipins. Conversely, the endogenous contents of NAEs and NAE‐oxylipin species, especially linoleoylethanolamide and 9‐hydroxy linoleoylethanolamide, were lower in PDP‐EA treated seedlings than in controls. Further, transcripts for endogenous cotton FAAH genes were increased following PDP‐EA exposure. Collectively, our data corroborate that the enhancement of FAAH enzyme activity by PDP‐EA stimulates NAE‐hydrolysis and that this results in enhanced growth in seedlings of a perennial crop species, extending the role of NAE metabolism in seedling development beyond the model annual plant species, Arabidopsis thaliana .